The Cardioprotective Effect of Corosolic Acid in the Diabetic Rats: A Possible Mechanism of the PPAR-γ Pathway - Faisal K. Alkholifi; Sushma Devi; Hasan S. Yusufoglu; Aftab Alam (Molecules, 2023)
The study was conducted to determine whether corosolic acid could protect the myocardium of diabetic rats from damage caused by isoproterenol (ISO) and, if so, how peroxisome proliferator-activated receptor gamma (PPAR-γ) activation might contribute into this protection. Diabetes in the rats was induced by streptozotocin (STZ), and it was divided into four groups: the diabetic control group, diabetic rats treated with corosolic acid, diabetic rats treated with GW9662, and diabetic rats treated with corosolic acid plus GW9662. The study was carried out for 28 days. The diabetic control and ISO control groups showed a decrease in mean arterial pressure (MAP) and diastolic arterial pressure (DAP) and an increase in systolic arterial pressure (SAP). The rat myocardium was activated by corosolic acid treatment, which elevated PPAR-γ expression. A histopathological analysis showed a significant reduction in myocardial damage by reducing myonecrosis and edema. It was found that myocardial levels of CK-MB and LDH levels were significantly increased after treatment with corosolic acid. By decreasing lipid peroxidation and increasing endogenous antioxidant levels, corosolic acid therapy showed a significant improvement over the ISO diabetic group. In conclusion, our results prove that corosolic acid can ameliorate ISO-induced acute myocardial injury in rats. Based on these results, corosolic acid seems to be a viable new target for the treatment of cardiovascular diseases and other diseases of a similar nature.